Organic-coated nanoparticulate zero valent iron for remediation of chemical oxygen demand (COD) and dissolved metals from tropical landfill leachate - Wijesekara, S. S. R. M. D. H. R; Basnayake, B. F. A; Vithanage, Meththika (Environmental science and pollution research international, 2014)
The use of nanoparticulate zero valent iron (NZVI) in the treatment of inorganic contaminants in landfill leachate and polluted plumes has been the subject of many studies, especially in temperate, developed countries. However, NZVI’s potential for reduction of chemical oxygen demand (COD) and treatment of metal ion mixtures has not been explored in detail. We investigated the efficiency of NZVI synthesized in the presence of starch, mercaptoacetic, mercaptosuccinic, or mercaptopropenoic acid for the reduction of COD, nutrients, and metal ions from landfill leachate in tropical Sri Lanka. Synthesized NZVI were characterized with X-ray diffraction (XRD), transmission electron microscopy, X-ray photoelectron spectroscopy, scanning electron microscopy (SEM), thermal gravimetric analysis, Fourier transform infrared spectroscopy (FTIR) and Brunauer–Emmett–Teller. Of the samples tested, Starch-NZVI (S-NZVI) and mercaptoacetic-NZVI (MA-NZVI) performed well for treatment both COD and metal mixture. The removal percentages for COD, nitrate-nitrogen, and phosphate from S-NZVI were 50, 88, and 99 %, respectively. Heavy metal removal was higher in S-NZVI (>95 %) than others. MA-NZVI, its oxidation products, and functional groups of its coating showed the maximum removal amounts for both Cu (56.27 mg g⁻¹) and Zn (28.38 mg g⁻¹). All mercapto-NZVI showed well-stabilized nature under FTIR and XRD investigations. Therefore, we suggest mercapto acids as better agents to enhance the air stability for NZVI since chemically bonded thiol and carbonyl groups actively participation for stabilization process.